Assessment of the prevalence and spatial distribution of the posterior superior alveolar artery within the maxillary sinus wall utilizing CBCT imaging - Maqbool, Maha; Ahmad Danyal; Zubair Ahmad Khan; Muhammad Haseeb; Usman Manzoor; Nuvaira Ijaz (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: The posterior superior alveolar (PSAA) artery plays a crucial role in supplying blood to the lateral wall of the maxillary sinus. This artery is of particular significance while performing procedures that involve the maxillary sinus. Our current study aimed to localize this artery and record its distance from a particular landmark: the maxillary sinus floor in patients reporting to a dental teaching hospital. METHODOLOGY: This cross-sectional study was conducted in the Department of Periodontology at Lahore Medical & Dental College. A total of 85 cone-beam computed tomography (CBCT) images were analyzed to document the presence and precise location of the posterior superior alveolar artery (PSAA). RESULTS: This study visualized 170 maxillary sinuses of 55 males and 30 females. The PSAA was visualized in 84.1 % of the sinuses. Further analysis revealed that in 54.1% of cases (n = 92), the artery was located intraosseously; in 21.2% (n = 36), it was situated below the sinus membrane; and in 8.8% (n = 15), it was found on the outer surface of the lateral wall of the maxillary sinus. The mean vertical distance from the lowest point of the sinus floor to the PSAA was 6.96 mm, with a range of 1.32 mm to 16.23 mm. CONCLUSIONS: Our study validates the diverse locations of the PSAA relative to the maxillary sinus’s lateral wall, with no notable differences observed between genders. Additionally, it highlights the effectiveness of CBCT as a reliable method for pre-surgical evaluation of the maxillary sinus and its associated blood vessels.